Extracorporeal Shockwave Therapy Increases Growth Factor Release from Equine Platelet-Rich Plasma In Vitro - Seabaugh, Kathryn A.; Thoresen, Merrilee; Giguère, Steeve (Frontiers in Veterinary Science, 2017)
Introduction Extracorporeal shockwave therapy (ESWT) and platelet-rich plasma (PRP) are common treatments for soft tissue injuries in horses. Shockwave triggers cell specific responses to promote healing. Growth factors released from PRP also promote healing. It has been hypothesized that greater growth factor release would amplify the healing process. The combination of ESWT and PRP could promote healing in injured tendons and ligaments in the horse. The objective of this study was to determine if application of shockwaves to PRP samples increases the concentration of transforming growth factor-β1 (TGF-β1) and platelet-derived growth factor ββ (PDGF-ββ) released from the platelets in vitro. Materials and methods PRP was produced from blood drawn from six horses. The PRP from each horse was exposed to the following treatments: (1) positive control (freeze-thaw cycle), (2) untreated negative control, or shockwaves with either (3) a “standard probe” (ESWT-S) with a 2 cm focal width and medium energy density or (4) a “power probe” (ESWT-P) with a 1 cm focal width and high energy density. After each treatment, the samples were centrifuged, and the supernatant was harvested. The supernatant was then used for growth factor quantification via commercially available ELISA kits for TGF-β1 and PDGF-ββ. Results Concentrations of TGF-β1 and PDGF-ββ in PRP that underwent a freeze-thaw cycle were significantly increased compared with all other treatments. Both ESWT-S and ESWT-P resulted in significantly increased TGF-β1 concentrations, 46 and 33%, respectively, when compared with the negative control. Both ESWT-S and ESWT-P resulted in significantly increased PDGF-ββ concentrations, 219 and 190%, respectively, when compared with the negative control. Discussion These data indicate that the application of ESWT to PRP increases the expression of growth factors in vitro. This suggests that the combination therapy of local PRP injection followed by ESWT may stimulate release of growth factors from platelets after they have been injected into the area of injury. Conclusion The combination of PRP and ESWT might result in synergism of two modalities previously utilized individually for tendon and ligament injuries in horses.